Optimized thermal pretreatment for lignocellulosic biomass of pigeon pea stalks to augment quality and quantity of biogas production - T. Sathish; K. Muthukumar; R. Saravanan; Jayant Giri (International Journal of Thermofluids)
By applying heat to the feedstock during the thermal treatment of biomass for the production of biogas, the organic material's biodegradability can be greatly increased. Biogas production is a huge research area for alternate energy production technology. Increased biodegradability, improved methane yield, pathogen, and weed seed destruction, and overall process efficiency are all benefits of this type of pretreatment. It is a useful pretreatment technique for maximizing the production of biogas because it can decrease inhibitory compounds, and increase the digestibility of biomass. This work focused on increasing the efficiency of biogas production from lignocellulosic biomass of pigeon pea stalks by a novel thermal pretreatment. The pigeon pea stalk is initially imposed to physical pretreatment (PT) by an automatic hammer mill which is considered as a base for comparing performance. Thermal pretreatment was carried out for one hour, and two hours durations at different temperatures like 100 °C, 125 °C, 150 °C, 175 °C, and 200 °C. Compared to physically pretreated pigeon pea stalks, 200ᴼC thermal pretreated pigeon pea stalks for two hours have produced 88.41 % higher biogas, 16.14 % increase of cellulose, 19.9 % higher volatile solid removal, and 3.94 % lesser lignin. The enhanced chemical characteristics were ensured by analyzing the chemical composition variations through the FTIR, XRD, and SEM images. So, this is recommended for enhanced biogas production.